ANALISIS KORELASI NILAI CALIFORNIA BEARING RATIO (CBR) DAN NILAI KUAT GESER PADA TANAH LUNAK - Sulistiawati, Baiq Heny; Goro, Garup Lambang; Junaidi, Junaidi; Isnubroto, Danang; Nurhadi, Imam (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2024)
The CBR value is influenced by soil gradation, mineral type, density and soil shear parameters. CBR testing is carried out on subgrade soil, but the undrained shear strength of the soil can also be used as a soil design parameter. Field shear strength tests that can be used to determine soil shear strength are DCP and Vane Shear. In contrast to DCP testing, shear strength testing is relatively quick and easy to determine soil properties to determine design parameters. Therefore, testing is needed to determine the correlation between the soil shear strength value and the CBR value to obtain a new equation that can be applied in the field. In this research, the CBR value was obtained through the Dynamic Cone Penetrometer test (DCP) and the soil shear strength of the vane shear test. DCP and Vane Shear testing was carried out at 10 test points in the Semarang area, Central Java. Laboratory testing is also carried out to validate soil types. The correlation obtained between the CBR value and the soil shear strength reached R = 0.8312. Based on this test, it can be concluded that the CBR value and soil shear strength value increase as the depth of the soil tested increases.